2009
DOI: 10.1007/s10482-009-9343-6
|View full text |Cite
|
Sign up to set email alerts
|

Ophiostomatoid fungi (Ascomycota) associated with Pinus tabuliformis infested by Dendroctonus valens (Coleoptera) in northern China and an assessment of their pathogenicity on mature trees

Abstract: Dendroctonus valens is an invasive pest in coniferous forests of northern China. It was suspected of being responsible for the death of more than three million Pinus tabuliformis trees. The present study sought to identify the ophiostomatoid fungi associated with D. valens in northern China and understand the possible role of these fungi in the pine decline. On the basis of morphology, physiology, mating compatibility and phylogenetic analyses of multiple DNA sequences, seven species of ophiostomatoid fungi we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(81 citation statements)
references
References 78 publications
1
80
0
Order By: Relevance
“…Pathogenicity has been tested for only L. sinoprocerum residing in the Asian lineages. This species was thought to be less pathogenic than the other fungal associates of D. valens based on the lesions resulting from inoculations in the crowns of mature P. tabuliformis in China (Lu et al 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenicity has been tested for only L. sinoprocerum residing in the Asian lineages. This species was thought to be less pathogenic than the other fungal associates of D. valens based on the lesions resulting from inoculations in the crowns of mature P. tabuliformis in China (Lu et al 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…In an extensive survey of ophiostomatoid fungi on P. densiflora its many bark beetle associates and their galleries L. yamaokae was isolated from only 10 of 20 Hylastes plumbeus galleries and from two of 48 beetles of this species (Masuya et al 2009 China (Lu et al 2009a, 2009b, Paciura et al 2010. Considering the absence of this species from these studies in the Far East and the large number of beetle species investigated by Masuya et al (2009), the association between L. yamaokae and H. plumbeus could be quite specific.…”
Section: Leptographiummentioning
confidence: 99%
“…Isolation studies revealed at least ten species of ophiostomatoid fungi including several from North America, as well as at least one strain from Europe (Q. Lu et al 2008;Lu et al 2009a). The rest were apparently acquired by the beetle in China.…”
Section: Anthropogenic Effectsmentioning
confidence: 99%
“…At this point, evidence indicates that the fungi alone are not responsible for the aggressiveness of this beetle in China. Rather, it is likely due to a combination of the fungi, a lack of coevolved resistance in the host tree, and drought stress (Lu et al 2009a).…”
Section: Anthropogenic Effectsmentioning
confidence: 99%